Mechanism of action of metformin as an anti-aging agent: a literature review - Aceng Hamudin; Nur Atik (DiscoverSys Inc., 2021)
Aging is a complex process consisting of various mechanisms that can cause damage and decrease the body's extrinsic and intrinsic functions. Metformin has been indicated for the treatment of degenerative diseases. It also has been reported to be used as an anti-aging agent. Various studies reported different mechanisms of action, but human studies are limited. This literature aims to review the multiple mechanisms of action of metformin as an anti-aging agent. Metformin has been reported to exert anti-aging effects by prolonging life in humans and animals. The effectiveness of metformin as an anti-aging agent is influenced by the dosage and age of the subjects studied. Various mechanisms of action of metformin concerning anti-aging have been reported, including autophagy pathways with AMPK activation and inhibition of mTOR, increased antioxidants, inhibition of ROS, inhibition or enhancement of mitochondrial function and inhibition of inflammation. It was found that there were biomarkers in the form of GPx7, Nrf2, PPAR and SREBP, SOD2, TrxR1, NQO1, NQO2, pNF-kB, FOXO, mTOR, AMPK, which could be used as predictors to explain the anti-aging effect of metformin.